Macrophages in Health and Non-Infectious Disease - Evgeny E. Bezsonov; Alexei Gratchev; Alexander N. Orekhov (Biomedicines, 2021)
In this Special Issue of Biomedicines, we have many insightful reviews and research papers on the subject “Macrophages in Health and Non-infectious Disease”, but first; we should discuss briefly the current situation in the field [...]